2015
DOI: 10.1534/g3.115.021899
|View full text |Cite
|
Sign up to set email alerts
|

Caenorhabditis elegans glp-4Encodes a Valyl Aminoacyl tRNA Synthetase

Abstract: Germline stem cell proliferation is necessary to populate the germline with sufficient numbers of cells for gametogenesis and for signaling the soma to control organismal properties such as aging. The Caenorhabditis elegans gene glp-4 was identified by the temperature-sensitive allele bn2 where mutants raised at the restrictive temperature produce adults that are essentially germ cell deficient, containing only a small number of stem cells arrested in the mitotic cycle but otherwise have a morphologically norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 56 publications
1
24
0
Order By: Relevance
“…We confirmed an increase in triacylglycerol stores using quantitative biochemical analysis of lipids in animals treated with wars-1 RNAi and animals bearing a temperature sensitive mutation in vars-2 (Figure S1A, vars-2 ( bn2ts ) also known as glp-4 ) (Rastogi et al, 2015). We similarly witnessed an increase in fat when worms were treated with the translation elongation inhibitor cycloheximide (Figure S1B) (Schneider-Poetsch et al, 2010).…”
Section: Resultssupporting
confidence: 56%
See 1 more Smart Citation
“…We confirmed an increase in triacylglycerol stores using quantitative biochemical analysis of lipids in animals treated with wars-1 RNAi and animals bearing a temperature sensitive mutation in vars-2 (Figure S1A, vars-2 ( bn2ts ) also known as glp-4 ) (Rastogi et al, 2015). We similarly witnessed an increase in fat when worms were treated with the translation elongation inhibitor cycloheximide (Figure S1B) (Schneider-Poetsch et al, 2010).…”
Section: Resultssupporting
confidence: 56%
“…The wild-type strain was N2 Bristol. The following C. elegans strains were used: MGH55 daf-16(mgDf47) 3×, CB4037 glp-1(e2141) , MGH274 aak-2(ok524) 4×, MGH275 aak-1 ( tm1944 ) 4×, MGH276 aak-1(tm1944) ; aak-2 ( ok524 ), NL2098 rrf-1(pk1417) 2×, NL3511 ppw-1(pk1425) 2×, GR1373 eri-1(mg366) 5×, AGD467 uthEx490 , SS104 vars-2/glp-4 ( bn2ts ) 2× (vars-2/glp-4(bn2ts) encodes missense mutation Gly296Asp (Rastogi et al, 2015)).…”
Section: Methodsmentioning
confidence: 99%
“…We also observed that glp-4(bn2) adults grown at the permissive temperature no longer exhibited a decrease in postdauer brood size in the starvation condition ( Fig 6B ), but continued to show an increased number of progeny in the pheromone condition ( Fig 6A ). Recently, GLP-4 was shown to be expressed in the intestine and somatic gonad in addition to the germ line [ 41 ]; thus, our observed glp-4 PD/CON brood size phenotype at the permissive temperature suggests that GLP-4 function in the intestine or somatic gonad is contributing to the regulation of the starvation program (see Discussion ).…”
Section: Resultsmentioning
confidence: 55%
“…Rather, we observed an enhancement of UVC-induced quiescence in glp-4 mutants. Since glp-4(bn2) has reduced efficiency of translation in somatic cells (Rastogi et al 2015), which may contribute to the altered phenotype following UV irradiation, we used another temperature-sensitive mutant to eliminate the germline: Figure 2 UVC exposure does not activate proteostatic stress response pathways. Adult animals of strains SJ4005 (promoter of hsp-4 driving GFP), TJ375 (promoter of hsp16.2 driving GFP), and SJ4100 (promoter of hsp-6 driving GFP) were imaged with bright field optics (rows 1,3, and 5) and with green fluorescence optics (rows 2, 4, and 6) 4 hr after heat shock at 33°for 30 min, UVC irradiation at 1500 J/m 2 , after cultivation on bacteria expressing double-stranded RNA known to induce mitochondrial stress, or untreated and cultivated on DA837 bacteria.…”
Section: Uvc-induced Quiescence Is Not Associated With Induction Of Pmentioning
confidence: 99%